1716 N.H. Laws 91, in 2 Laws of New Hampshire: Province Period 285 (Albert Stillman Batchellor ed., 1904) (enacted 1718) - (:unkn) unknown (My University, 1718)
Required every "householder" to have a musket, bandoliers, cartridge box, bullets, powder, cleaning tools, and a sword. Penalty of six schillings for each arm and two schillings for each other defect.
Keywords: REQUIRED POSSESSION